Brain-derived neurotrophic factor (BDNF) in children with ASD and their parents: a 3-year follow-up - Francis,K.; Dougali,A.; Sideri,K.; Kroupis, C.; Vasdekis,V.; Dima, K.; Douzenis, A. (Acta Psychiatr.Scand., 2018)
OBJECTIVE: Several lines of evidence point to a probable relationship between brain-derived neurotrophic factor (BDNF) and autism spectrum disorder (ASD), but studies have yielded inconsistent findings on the BDNF serum level in ASD. The study aimed to assess those levels in children with ASD and their families. METHOD: BDNF serum levels were measured in 45 ASD children without intellectual disability (ID) and allergies, age 30-42 months and age-matched normal controls. BDNF serum levels in the parents of the ASD subjects were compared to normal controls. BDNF serum levels in the ASD subjects were followed up for 3 years and correlated with adaptive functioning changes. RESULTS: BDNF serum levels were measured to be lower in children with ASD and independent of all the major baseline characteristics of the subjects. Having a child with ASD raises the BDNF levels in parents comparing to controls. Prospectively, no correlation between the change of BDNF variables in time and the change of the Vineland scores was found. CONCLUSIONS: Our results contradict those from recent published meta-analyses with the age, the presence of ID and allergies being possible contributing factors. The parents' data indeed point to a role of BDNF in the pathophysiology of ASD
IS - 1600-0447 (Electronic) IS - 0001-690X (Linking) LA - eng PT - Journal Article
Keywords: Adolescent; Greece